1994
DOI: 10.1099/0022-1317-75-7-1623
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-mediated inhibition of phorbol ester and Tax trans-activation of the human T cell leukaemia virus type 1

Abstract: Human Jurkat T cells containing a stably integrated human T cell leukaemia virus type 1 (HTLV-1) long terminal repeat (LTR) reporter gene construct were used to study the role of calcium-dependent cellular activation pathways in LTR trans-activation. Treatment of these cells with the calcium ionophore ionomycin resulted in a reduced basal response of the LTR and reduced responses to 12-O-tetradecanoylphorbol-13-acetate-and Tax-mediated trans-activation. This effect was also observed for virus production in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
1
Order By: Relevance
“…Another marked difference concerns the calcium-dependent pathway. In the HTLV system, the calcium ionophore ionomycin reduced viral expression (9). This is in sharp contrast with our data for the BLV system, which show that A23187 appears to be the most potent activator of viral expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Another marked difference concerns the calcium-dependent pathway. In the HTLV system, the calcium ionophore ionomycin reduced viral expression (9). This is in sharp contrast with our data for the BLV system, which show that A23187 appears to be the most potent activator of viral expression.…”
Section: Discussioncontrasting
confidence: 99%
“…A study using CD4 + T-cell lines experimentally infected with HTLV-1 also showed that CD3 high and CD3 low T-cells had the same capacity to express the HTLV-1 core protein (Willard-Gallo et al , 2001). Moreover, despite the structural and functional homology between HTLV-1 and BLV, treatment with a calcium ionophore reduced viral expression in HTLV-1-infected T-cells (Copeland et al , 1994), whereas it was upregulated in BLV-infected B-cells (Kerkhofs et al , 1996). Previous reports and the results obtained in the present study suggest that HTLV-1-infected T-cells and BLV-infected B-cells may use different signalling pathways and strategies to express viral antigens and to expand their infection to uninfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 LTR-mediated transcription was increased by TPA, and this response was further enhanced by the calcium (Ca 2ϩ ) ionophore ionomycin. In contrast, the induction of the HTLV-1 LTR by TPA was inhibited by ionomycin (58,59,61), suggesting that the triggering of Ca 2ϩ -dependent pathways in the cell could adversely affect virus expression. Further experiments revealed that the ionomycin-mediated inhibition was not restricted to TPA-induced activation mechanisms, since basal LTR activity and Tax-mediated activation were also compromised by ionomycin.…”
Section: Effect Of T Helper Cell Activation On Retroviral Expressionmentioning
confidence: 99%
“…This condition of immune system activation is further supported by the ability of the infected Th cell to maintain the activated state for prolonged periods in an IL-2-independent manner (146,353). We have postulated that Th-cell activation down-regulates HTLV expression (59,61). Hollsberg et al (145) have reported that HTLV-1 mediates T-cell activation through a pathway which is insensitive to the immunosuppressive cytokine TGF-␤1.…”
Section: Htlv and Atlmentioning
confidence: 99%